Acute spinal cord infarction secondary to ankylosing spondylitis: a case report and literature review - Li, Wenjuan; Guo, Jia; Wang, Lei; Zhang, Tinghua; Li, Tian (Frontiers in Neurology, 2023)
Introduction Spinal cord infarction secondary to ankylosing spondylitis is a rare but severe disorder. Case presentation Here we present a case of acute spinal cord infarction in a 54 years-old man with a medical history of ankylosing spondylitis, scoliosis, and hypotension. The patient complained of a sudden onset of lower limb weakness. A physical examination showed that he suffered from a dissociative sensory disorder, paralysis, and concomitant sphincter disturbances. After undergoing a whole-spine MRI, he was diagnosed with an acute ischemic injury from T2 to T5. As he did not treat his ankylosing spondylitis, it later caused a spinal deformity, making the lumbar puncture technically challenging. However, using Taylor’s approach, a CSF sample was successfully obtained. A CSF biochemical test ruled out myelitis, NMOSD, and MS. After receiving treatment with low-molecular-weight heparin, atorvastatin calcium, and methylprednisolone, his sphincter function gradually recovered, but his strength was only partially restored. Conclusion Although this is a rare entity, it is necessary for physicians to consider it when evaluating patients with a sudden loss of sensation and strength in their lower limbs.